Analisis Resiko Lingkungan dalam Pembangunan Gedung di Atas Tanah Lunak - Anwar, Roy Rizali; Pratikso, Pratikso; Wibowo, Kartono; Wardiningsih, S. (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
Construction projects around the world have a significant impact on the environment where construction is being built, both on a local and global scale. Each stage of the construction process has a measurable environmental impact, including the process of mining the materials used to obtain raw materials, transporting these materials to the location, noise, dust caused by the use of heavy equipment, and the waste disposal process after completion of construction. With a rapidly developing global economy, it is important to understand the impact of construction projects on the environment and how it can be reduced this impact in the future. This research aims to analyze risks that occur in the environment which generally happen in building construction using variables from the results of a review of several journals related to environmental impacts. The method used in this research is a quantitative method based on data collecting from the questionnaires. The results obtained show that the most important factors that influence the environment are noise (30%), dust (24%), road damage (20%), and the amount of waste after construction (9%).